Surmounting Obstacles in STEM Education: An In-depth Analysis of Literature Paving the Way for Proficient Pedagogy in STEM Learning - Salvetti, Fernando; Rijal, Khaerul; Owusu-Darko, Isaac; Prayogi, Saiful (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2023)
The modern educational system has recognized the significance of STEM as a vital component of students' preparation for a promising future. Consequently, there is a need for comprehensive research in STEM education, encompassing an understanding of its context, challenges, and strategies to overcome these obstacles. Ongoing research continues to focus on developing coherent studies in this area, particularly emphasizing effective STEM pedagogy, which has proven to positively impact students' learning outcomes. However, despite its potential, STEM education faces several challenges that could impede its progress. In the scope of this study, a thorough examination revealed at least six key challenges confronting, these challenges encompass: pedagogical challenges, curriculum-related issues, structural complexities, student apprehensions, assessment concerns, and the critical need for teacher support. These challenges, along with proposed solutions, are discussed in-depth in this article. It is worth noting that pedagogical challenges hold paramount importance, as teachers play a pivotal role in implementing successful STEM education in schools. As such, this article delves into various effective pedagogical aspects that can facilitate the advancement of STEM education and foster enhanced learning experiences for students. Several key aspects contribute to effective pedagogy in STEM education and learning, including: (a) cultivating an innovative learning environment that nurtures inquiry, experimentation, and critical thinking; (b) utilizing a diverse range of authentic learning methods and relevant educational resources; (c) facilitating a collaborative learning environment that encourages teamwork and knowledge sharing; (d) creating an inclusive learning environment that accommodates the diverse needs of students; and (e) encouraging continuous reflection on and improvement of teaching practices to optimize learning outcomes.